Transient Analysis And Optimization Of A Knuckle Joint - Muhammad, Aisha; Shanono, Ibrahim Haruna (Universitas Muhammadiyah Malang, 2019)
Knuckle joint is used to provide movement between rods while transferring force along the pin axis. It has a range of applications such as in robotics, reciprocating engine valve, fulcrum, and suspension bridge. Various cases have been reported of failures in a Knuckle joint due to poor design and strenuous loading condition. For a guaranteed safety of the structure, analysis and optimization of a knuckle joint are required. A cheaper and qualitative production of the knuckle joint can be achieved in a short period through optimization. In this paper, Finite Element Method (FEM) using ANSYS workbench was used to carry out topology optimization, and transient analysis of a knuckle joint where its dynamic response is observed and its weight is reduced through optimization under certain design loading conditions. Weight reduction of 20%, 35%, and 50% using a structural steel material under a static loading of 1000N. The optimization process successfully identifies the mass that needs to be removed to minimize both weight and cost without compromising its reliability and durability. The structural design was carried out using SolidWorks software and then imported into the ANSYS workbench for analysis. By the results obtained, it is proved that ANSYS software can be employed by production companies to minimize material wastages and maximize profits while at the same time maintaining product quality and reliability